Corrosion study on welded mild steel in soil environment - Mohamed Rais Mohamed (Universiti Malaysia Perlis, 2008)
This study was carried out to determine the corrosion behavior of welded mild steel in soil environment. The welding process was done by arc welding method at 70, 80, 90, 100 and 110 ampere. The corrosion behavior of welded mild steel was studied by immersion and typical electrochemical method. This study was focuses on the corrosion behavior at weld metal region and heat affected zone (HAZ) which is known as the highest risk to corrosion attack compare to base metal. The effect of microstructure changes in welded mild steel induced by the processes of arc welding on the pitting and corrosion cracking behaviors was investigated. Pitting was evaluated by metallographic method and observed under metallurgical microscope. Immersion was carried out for 30 days in backfill as electrolyte and weight loss from the sample was calculated to achieve the corrosion rate for each sample. Open circuit potential welded mild steel show the different potential during corrosion in soil environment. Potentiodynamic polarization and Tafel plots were used to determine the corrosion behavior of the welded mild steel in closed circuit.